2016
DOI: 10.1002/rcm.7538
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic profiling of new synthetic cannabinoids AMB and 5F‐AMB by human hepatocyte and liver microsome incubations and high‐resolution mass spectrometry

Abstract: For the first time, AMB and 5F-AMB metabolism profiles were characterized, providing valuable data for identifying these two novel psychoactive substances. The difficulties of differentiating AMB and 5F-AMB from AB-PINACA/5F-AB-PINACA metabolites also were examined. These data improve the interpretation of urinary markers after AMB and 5F-AMB intake. Published in 2016. This article is a U.S. Government work and is in the public domain in the USA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
66
0
1

Year Published

2016
2016
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(78 citation statements)
references
References 32 publications
(86 reference statements)
11
66
0
1
Order By: Relevance
“…A thorough understanding of these processes is important for determining drug toxicology and for identifying these compounds in biological matrices where they are likely extensively metabolized [1315]. A precise understanding of metabolic pathways is necessary, because closely structurally related synthetic cannabinoids can produce identical metabolites, which can increase the difficulty of forensic identification of a unique compound [13, 15]. In addition, some synthetic cannabinoid metabolites retain cannabinoid receptor efficacy and therefore may be relevant to the overall pharmacological profile following drug administration [16, 17].…”
Section: Introductionmentioning
confidence: 99%
“…A thorough understanding of these processes is important for determining drug toxicology and for identifying these compounds in biological matrices where they are likely extensively metabolized [1315]. A precise understanding of metabolic pathways is necessary, because closely structurally related synthetic cannabinoids can produce identical metabolites, which can increase the difficulty of forensic identification of a unique compound [13, 15]. In addition, some synthetic cannabinoid metabolites retain cannabinoid receptor efficacy and therefore may be relevant to the overall pharmacological profile following drug administration [16, 17].…”
Section: Introductionmentioning
confidence: 99%
“…However, drivers taking indazole carboxamide SCs frequently showed rapid recovery within an hour. It has been reported that 5F-AMB is quickly hydrolyzed by hepatic esterase [20], while 5F-AB-PINACA is more slowly metabolized to various products [21]. The rapid recovery seen in this class of SC remains mysterious.…”
Section: Lineage and Timeline Of Scmentioning
confidence: 99%
“…To date, all investigated SCs are extensively metabolized in humans and are predominantly excreted as metabolites in urine [6, 16, 22, 23], complicating detection, as metabolites are initially unknown. Knowledge of human metabolism is essential for verifying NM-2201 consumption since urine testing is routine for workplace, clinical and forensic testing.…”
Section: Introductionmentioning
confidence: 99%